2014
DOI: 10.1185/03007995.2014.938730
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns in metastatic renal cell carcinoma: a retrospective review of medical records from US community oncology practices

Abstract: Vol. 30, No. 10, 2014, 2041-2050

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
36
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 26 publications
7
36
2
Order By: Relevance
“…This study builds on and adds to earlier descriptions of treatment patterns, which included much smaller numbers of patients receiving recently approved treatments. 11,[19][20][21][22][23][24] The results of the present study showed that, at initiation of the second targeted therapy, patients' characteristics differed across treatments. In particular, lung metastases were observed more frequently in patients treated with everolimus and axitinib than in patients treated with sorafenib or sunitinib.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study builds on and adds to earlier descriptions of treatment patterns, which included much smaller numbers of patients receiving recently approved treatments. 11,[19][20][21][22][23][24] The results of the present study showed that, at initiation of the second targeted therapy, patients' characteristics differed across treatments. In particular, lung metastases were observed more frequently in patients treated with everolimus and axitinib than in patients treated with sorafenib or sunitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our previous treatment pattern study conducted in 2012, sunitinib remained the most frequently used first targeted therapy, whereas everolimus remained the most frequently used second targeted therapy. 11 Furthermore, the use of pazopanib as first targeted therapy and of axitinib and sorafenib as second targeted therapies increased over time. A recent phase III trial (AXIS) has shown that, although axitinib is associated with longer progression-free survival than sorafenib, the overall survival results are comparable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations